Electrical stability study of polymer-based organic transistors in ambient air using an active semiconducting/insulating polyblend-based pseudo-bilayer. (4th May 2020) - Lin, Bo-Ren; Cheng, Horng-Long; Lin, Hung-Han; Wu, Fu-Chiao; Lin, Jia-Hui; Chou, Wei-Yang; Ruan, Jrjeng; Wang, Yu-Wu
Abstract : Polymeric transistors with unexpected nondecaying features even in ambient air are fabricated based on a P3HT/PMMA pseudo-bilayer with microphase separation morphology. Abstract : Organic thin-film transistors (OTFTs) often exhibit significant nonideal, unstable, and fast decaying electrical characteristics, especially in a moisture-containing ambient air environment, which hinders their practical applications. These characteristics are particularly true for OTFTs based on the widely studied poly(3-hexylthiophene) (P3HT) active layer. This study reports that dynamic operational stability of P3HT-based OTFTs even in ambient air can be achieved through the preparation of a semiconducting/insulating polyblend-based pseudo-bilayer configuration with embedded source and drain electrodes. The pseudo-bilayer active layer with desired phase-separated morphology, which consists of insulating poly(methyl methacrylate)-rich round domains and a highly connected network of conducting P3HT channels, was specifically developed and optimized for OTFTs. The present OTFTs can perform with strong endurance against gate-bias stress even under dynamic continuous operation in ambient air, and thus show unexpected nondecaying current features. We investigated the possible origins behind the excellent operational and environmental stability of the pseudo-bilayer-based OTFTs in terms of atomic force microscopy, electrostatic force microscopy, X-ray diffractometry, absorption spectroscopy, Raman spectroscopy, in situ photoluminescence spectroscopy, and quantum chemical calculations. Finally, a gas-induced electrical response mechanism of polymeric OTFTs at the microscopic level was also proposed on the basis of the charge delocalization variation in the semiconducting component. Thus, insight into the impact of ambient gases on the electrical stability of OTFTs was realized. The results provide insight into the solution for the long-standing electrical stability problem of OTFTs under continuous operation through the development of improved fabrication techniques.